The a to Z of Norway - Sjåvik, Jan (Rowman & Littlefield Publishers, 2010)
One of the smallest countries in Europe, Norway has created for itself a position in the world community, which is completely out of proportion to the size of its population. Originally the home of sub-Arctic hunters and gatherers, then of ferocious Vikings, it lost perhaps half of its population to the Black Death in 1349, ended up in a union with Denmark that lasted until 1814, and then became united with Sweden, gaining complete independence only as recently as 1905. Over the centuries the Norwegians eked out a meager living from stony fields and treacherous seas while suffering through hunger, darkness, and cold, however, its recent productive use of such natural resources as hydroelectric power, natural gas, and oil has made the Norwegians some of the richest people in the world. The A to Z of Norway supplies a wealth of information that illuminates Norway's remarkable history, society, and culture. This is done through a chronology, a bibliography, an introductory essay, appendixes, and over 250 cross-referenced dictionary entries covering events and individuals of historical, political, social, and cultural significance. Both past and present political parties are discussed, major economic sectors are described, and basic economic facts are provided. Several entries describe the history and attractions of major Norwegian cities, and Norway's role in the international community is detailed as well providing a full portrait of this vibrant country.